1993
DOI: 10.1161/01.hyp.21.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose does not raise blood pressure in rats maintained on a low salt intake.

Abstract: Diets high in sucrose or fructose have been shown by others to induce a modest elevation of blood pressure in rats. The present experiments were conducted to determine whether the sucrose-induced increase of blood pressure is dependent on the intake of sodium chloride. Four groups of Sprague-Dawley rats were studied: 1) a group maintained on a low salt diet and distilled water (0.45% sodium chloride, no added sucrose), 2) a low salt-high sucrose group (0.45% sodium chloride diet and 7% sucrose in distilled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 27 publications
1
14
2
Order By: Relevance
“…Although several reports indicate fructose as a factor involved in hypertension (4,5,9), several investigators have failed to observe an increase in blood pressure in fructose-fed rats (31,32). These apparently conflicting data have been attributed to differences in the composition of the diets and to variable blood pressure responses to fructose among different ages and strains of normotensive rats (31,32). We observed no significant difference in blood pressure between the highfructose and control groups.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Although several reports indicate fructose as a factor involved in hypertension (4,5,9), several investigators have failed to observe an increase in blood pressure in fructose-fed rats (31,32). These apparently conflicting data have been attributed to differences in the composition of the diets and to variable blood pressure responses to fructose among different ages and strains of normotensive rats (31,32). We observed no significant difference in blood pressure between the highfructose and control groups.…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, the AT 1 receptor antagonist losartan and an angiotensin-converting enzyme inhibitor attenuated the magnitude of the blood pressure elevation and improved insulin sensitivity in fructose-fed rats (28)(29)(30). Although several reports indicate fructose as a factor involved in hypertension (4,5,9), several investigators have failed to observe an increase in blood pressure in fructose-fed rats (31,32). These apparently conflicting data have been attributed to differences in the composition of the diets and to variable blood pressure responses to fructose among different ages and strains of normotensive rats (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia is frequently associated with sucrose-and fructose-induced hypertension [18], and the increase in sympathetic nervous activity [24] and renal sodium retention caused by hyperinsulinemia [25] might be plausible explanations for the genesis of hypertension. However, insulin resistance or hyperinsulinemia has not been shown in all studies of fructose-or sucrose-induced hypertension [17,[26][27][28]. In this current study, we could find no relationship between the increase in blood pressure and fasting plasma insulin and/or glucose level.…”
Section: Discussioncontrasting
confidence: 82%
“…Hypertension-induced insulin resistance has been demonstrated to accompany increased skeletal muscle vascular resistance (25). Additionally, it has been reported that sucrose feeding increases norepinephrine excretion, turnover, and plasma concentration and enhances sympathetic nerve responses in rats (26,27). Thus sympathetic overactivity may be involved in the pathogenesis of this model, and may be responsible at least in part for the impairment of blood flow to skeletal muscle, which in turn would favor the development of insulin resistance (28).…”
Section: Discussionmentioning
confidence: 99%